2011
DOI: 10.1007/s10278-011-9390-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Doses in CR Examinations Throughout a Large Health Region

Abstract: Optimization and standardization of radiographic procedures in a health region minimizes patient exposure while producing diagnostic images. This report highlights the dose variation in common computed radiography (CR) examinations throughout a large health region. The RadChex cassette was used to measure the radiation exposure at the table or wall bucky in 20 CR rooms, in seven hospitals, using CR technology from two vendors. Exposures were made to simulate patient exposure (21 cm polymethyl methacrylate) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Optimal exposure is necessary for accurate diagnosis as well as adherence to the ALARA principle. Underexposed images results in increased quantum mottle, reduced image quality of the radiograph and may impede diagnosis . Overexposure reduces quantum mottle, improving image quality, and is less likely to be rejected by radiologists; thus there is a trend towards this technique .…”
Section: Introductionmentioning
confidence: 99%
“…Optimal exposure is necessary for accurate diagnosis as well as adherence to the ALARA principle. Underexposed images results in increased quantum mottle, reduced image quality of the radiograph and may impede diagnosis . Overexposure reduces quantum mottle, improving image quality, and is less likely to be rejected by radiologists; thus there is a trend towards this technique .…”
Section: Introductionmentioning
confidence: 99%
“…From The Journal of Digital Imaging, a case-control observational study conducted by Thakur et al (2012) highlighted the dose variation in common CT examinations throughout a large health region. RadChex was the device used to measure radiation exposure on patients already undergoing computed radiography.…”
Section: Exposure Levelsmentioning
confidence: 99%
“…Patients undergoing CT scans in twenty different CT rooms throughout seven hospitals were included in the study. Thakur et al (2012) identified up to 30% of a patient's radiation dose may be reduced with standardization of AEC device. Within a large health region, variation in exam protocols can occur, leading to unnecessary patient dose from the same type of examination (Thakur et al, 2012).…”
Section: Exposure Levelsmentioning
confidence: 99%
See 2 more Smart Citations